Features of non-algorithmic methods in the teaching of elementary mathematics and their role in solving problems - Axmedova Nilufar Mamasidiqovna; Abdullayeva Marifat (International Journal on Orange Technologies, 2021)
This article is devoted to non-algorithmic learning methods. The article describes situations where the degree of certainty of the question posed requires students to be creative and independent.